Internal Trade in Canada : Case for Liberalization - Alvarez, Jorge (IMF Working Papers; Working Paper ;, 2019)
This paper assesses the costs of internal trade barriers and proposes policies to improve internal trade. Estimates suggest that complete liberalization of internal trade in goods can increase GDP per capita by about 4 percent and reallocate employment towards provinces that experience large productivity gains from trade. The positive impact highlights the need for federal, provincial and territorial governments to work together to reduce internal trade barriers. There is significant scope to build on the new Canadian Free Trade Agreement to more explicitly identify key trade restrictions, resolve differences, and agree on cooperative solutions.